Access to Specialist Gastroenterology Care in Canada: The Practice Audit in Gastroenterology (PAGE) Wait Times Program - David Armstrong; Alan NG Barkun; Ying Chen; Sandra Daniels; Roger Hollingworth; Richard H Hunt; Desmond Leddin (Canadian Journal of Gastroenterology)
BACKGROUND: Canadian wait time data are available for the treatment of cancer and heart disease, as well as for joint replacement, cataract surgery and diagnostic imaging procedures. Wait times for gastroenterology consultation and procedures have not been studied, although digestive diseases pose a greater economic burden in Canada than cancer or heart disease.